Застосування препарату альфа-ліпоєвої кислоти у лікуванні поопераційних дисфоній - Паламарчук, В. О.; Горобейко, М. Б. (Clinical Endocrinology and Endocrine Surgery, 2009)
In our study we presented new approach to improvement of treatment of disphonic disorder after thyroid operations. Efficiency of adding of α-lipoic acids "Berlition 600" to the standard protocol of treatment. 31 patients were examined and distributed on basic (16 patients which additionally to basic treatment received "Berlition 600") versus control group (15 patients). A reliable improvement of larynx phonation function took place in the patients of control group in 53% cases versus 75% in the study group. A has positive clinical effect Chosen medication in complex treatment of post-operative disphonic disorder after thyroid operations in cases of clinical signs of violation of mobility of elements of larynx.